Manejo cultural do maracujazeiro-amarelo em ciclo anual visando à convivência com o vírus do endurecimento dos frutos: um estudo de caso - Sampaio, Aloísio Costa [UNESP]; Scudeller, Nilton; Fumis, Terezinha de Fátima [UNESP]; De Almeida, Aparecida Marques; Pinotti, Raquel Nakasato; De Marchi Garcia, Maria Jose; Pallamin, Maria Lucia [UNESP] (Soc Brasileira Fruticultura, 2008)
This case study aimed to analyze the quality of fruits and productivity in t/ha of the yellow passion fruit in two annual cycles, respectively on October 4(th), 2004 (1(st) planting) and August 20(th), 2005 (2(nd) planting). In the 1(st) planting it was eradicated on the July 13(th), 2005, in function of the orchard presenting the totality of the plants with typical symptoms of PWV in fruits and leaves. The seedlings of the selection Afruvec were formed in plastic tubes inside greenhouse with anti-aphid screen. The orchard in both productive cycles was irrigated by leaking being adopted a density of 1.600 plants per hectare. In both plantings there was no necessity of elimination of plants, since the beginning of the symptoms of PWV happened when the plants were in the middle of the flowering. In the 1(st) planting the symptoms began on the January 26(th), 2005 and in the 2(nd) planting, on the January 4(th), 2006. For the results, it can be concluded that the regionally handling adopted with annual cycle planting, allowed an amplification of the crop period, due to the planting anticipation of the 2(nd) year, productivity of 16,94 kg/plant and 18,39 kg/plant, in the 1(st) and 2(nd) year, respectively; increase the profitability in the crop of 2006 in function of the best production and quotation of the fruits in natura and for industry; and mainly, a reduction of the potential of regional inoculum, seeking a sustainable production.
Handing of the of yellow passion fruit plant in annual cycle aiming the coexistence with the PWV (passion fruit woodiness virus): A case study
Keywords: Passiflora edulis Sims f. flavicarpa Deg.; sustainability; viruses